2019
DOI: 10.2196/12745
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App to Assist Smoking Cessation Among Aboriginal Australians: Findings From a Pilot Randomized Controlled Trial

Abstract: Background Mobile health (mHealth) apps have the potential to increase smoking cessation, but little research has been conducted with Aboriginal communities in Australia. Objective We conducted a pilot study to assess the feasibility and acceptability and explore the effectiveness of a novel mHealth app to assist Aboriginal people to quit smoking. Methods A pilot randomized controlled trial (RCT) and process evaluation comprising usage analyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 24 publications
3
66
1
1
Order By: Relevance
“…Qualitative analysis was performed with four studies, but the quantitative analysis was only carried out with the studies of Buller et al 35 , Danaher al. 34 , and Baskerville et al 36 , given the impossibility of calculating the RR for the study by Peiris et al 33 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative analysis was performed with four studies, but the quantitative analysis was only carried out with the studies of Buller et al 35 , Danaher al. 34 , and Baskerville et al 36 , given the impossibility of calculating the RR for the study by Peiris et al 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, four of them compared different versions of the same application (one more extensive version and another much smaller), and 1 was not a clinical trial but a cross-sectional study evaluating the characteristics of users of web-based programs or websites for mobiles ( Figure 1 ). The characteristics of the four studies 33 - 36 selected are summarized in Table 1 . Qualitative analysis was performed with four studies, but the quantitative analysis was only carried out with the studies of Buller et al 35 , Danaher al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has only been one trial of a targeted smoking cessation app for Aboriginal and Torres Strait Islanders, which had poor uptake and implementation challenges impacting on feasibility, which demonstrates the challenges of research in this field [ 39 ]. The uptake of the app might have been different if the app had been available on ‘general release’ through app stores [ 39 ]. The trustworthiness of apps or the lack of culturally targeted apps may reflect the lower use of apps in the women we surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…The general exploration of mHealth or eHealth applications among adults supports the feasibility and indicates a general interest in technologies, though economic and connectivity limitations in rural and remote areas are always a strong concern. 15 , 21 23 None of the products reviewed in a recent systematic review of mHealth technologies who engaged Indigenous communities included products specific to issues of aging. 24 Finally, with dementia-specific surveillance technology research, not one of the surveillance technology products described in several systematic reviews reported the inclusion of Indigenous or American Indian communities.…”
Section: Introductionmentioning
confidence: 99%